Yield components and bromatological composition of three Megathyrsus maximus cultivars in Guayas area, Ecuador - Méndez-Martínez, Y.; Reyes-Pérez, J. J.; Luna-Murillo, R.; Verdecia, D. M.; Rivero-Herrada, Marisol; Montenegro-Vivas, L.; Herrera, R. S. (Cuban Journal of Agricultural Science, 2019)
With the objective of evaluating the yield components and bromatological composition of three Megathyrsus maximus cultivars in Guayas area, Ecuador at different regrowth ages, the research was carried out, following a random block design with factorial arrangement (3x3) with five replications. The productivity (yields of total dry matter, leaves, stem and biomass), morphological components (plant height, length and width of leaves, number of leaves and stems) were studied; as well as the contents of DM, CP, NDF, ADF, ADL, cellulose (Cel), hemicellulose (Hcel), cellular content (CC), P, Ca, ash, OM, DMD, OMD, ME, LNE and the relations NDF-N and ADF-N at the ages of 21, 42 and 63 days. Analysis of variance was performed according to experimental design. The highest yields of DM and biomass were obtained in Tanzania at 63 days of regrowth (2.74 and 8.25 t/ha, respectively). The highest DM and biomass yields were obtained in Tanzania at 63 days of regrowth (4.18 and 12 t/ha, respectively). The CP and CC decreased with the maturity of the plant and the best values were obtained in Tanzania at 21 days of regrowth (15.67 and 62.16 %, respectively), while the components of the cell wall increased with age and Tanzania showed the best values. There was significant interaction between varieties and maturity (P <0.0001) for all indicators. It is concluded that the studied varieties show adequate productive performance under conditions of low rainfalls. The Tanzania and Tobiata cultivars are a good option to replace the food deficit during the dry period due to its higher proportion of leaves, better relations NDF-N and ADF-N that give it higher quality. Key words: yield, regrowth age, Megathyrsus maximus, chemical composition, digestibility, energy